Carbon stock quantification and climate mitigation potential of a tropical moist forest in Ethiopia. - Alemayehu K Shembo; Teshome Soromessa; Sebsebe Demissew; Addisie Geremew; Ram L Ray; Laura Carson (PLoS ONE)
The significance of forests in absorbing and storing carbon plays a crucial role in international greenhouse gas policies outlined by the United Nations Framework Convention for Climate Change (UNFCC). This study was conducted in a typical tropical moist forest of Ethiopia to assess its carbon stock, a critical issue in climate policy. The study domain was divided into six strata using elevation criteria. Ninety sample plots were used to gather relevant data from all carbon pools (above-ground biomass, below-ground biomass, litter, herbs, lying dead woods, and soils) following the standard operating procedure. ANOVA, post hoc analysis and correlation tests were used to analyze the collected data. The finding revealed that carbon stock in Sele-Nono forest varies not only within its carbon pools but also across environmental factors. Moreover, the study indicated that soil, above-ground biomass, and lying dead woods store the majority of the carbon. The forest stored 284.81±107.81 tons of carbon per hectare, which is equivalent to absorbing 157.12 Megatons of CO2 from the atmosphere. This highlights the critical role of the forest in mitigating climate change on a global scale. The finding from this study encourages policymakers to rigorously focus on forest conservation as a strategy for sustainable climate mitigation. Moreover, conserving forests through strengthening UN initiatives like REDD+ is imperative to prevent potential emissions from land use changes, such as deforestation or degradation.